Complete Genome Sequence of Paenibacillus strain Y4.12MC10, a Novel Paenibacillus lautus strain Isolated from Obsidian Hot Spring in Yellowstone National Park. Issue 3 (May 2012) - Mead, David; Lucas, Susan; Copeland, Alex; Lapidus, Alla; Cheng, Jan-Feng; Bruce, David; Goodwin, Lynne; Pitluck, Sam; Chertkov, Olga; Zhang, Xiaojing; Detter, John; Han, Cliff; et al.
Abstract Paenibacillus sp. Y412MC10 was one of a number of organisms isolated from Obsidian Hot Spring, Yellowstone National Park, Montana, USA under permit from the National Park Service. The isolate was initially classified as aGeobacillus sp. Y412MC10 based on its isolation conditions and similarity to other organisms isolated from hot springs at Yellowstone National Park. Comparison of 16 S rRNA sequences within theBacillales indicated thatGeobacillus sp. Y412MC10 clustered withPaenibacillus species, and the organism was most closely related toPaenibacillus lautus . Lucigen Corp. prepared genomic DNA and the genome was sequenced, assembled, and annotated by the DOE Joint Genome Institute. The genome sequence was deposited at the NCBI in October 2009 (NC_013406). The genome ofPaenibacillus sp. Y412MC10 consists of one circular chromosome of 7, 121, 665 bp with an average G+C content of 51.2%. Comparison to otherPaenibacillus species shows the organism lacks nitrogen fixation, antibiotic production and social interaction genes reported in other paenibacilli. The Y412MC10 genome shows a high level of synteny and homology to the draft sequence of Paenibacillus sp. HGF5, an organism from the Human Microbiome Project (HMP) Reference Genomes. This, combined with genomic CAZyme analysis, suggests an intestinal, rather than environmental origin for Y412MC10.